2021
DOI: 10.1520/jte20200123
|View full text |Cite
|
Sign up to set email alerts
|

Characterization Shear Properties of PVC Foams Instrumented by Optical Fiber under Flexural Loading

Abstract: The bending behavior of foam core sandwich composites has increasingly attracted attention and application in industries such as shipbuilding, aircraft and wind turbine industries. The main objective of this research work is the assessment of shear strain in a foam core beam by means of optical fiber sensors during bending test. Experimental studies were conducted on a PVC foam beam in which three optical fibers were embedded in a longitudinal plane across the thickness of the foam core; straight optical fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…In recent years, the highway pavement construction industry has rapidly progressed at the global scale due to the dramatic increase in traffic loads. Many studies on improving the quality of road materials have been reported recently [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the highway pavement construction industry has rapidly progressed at the global scale due to the dramatic increase in traffic loads. Many studies on improving the quality of road materials have been reported recently [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%